2018
DOI: 10.1016/j.ecoenv.2018.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac biomarkers as sensitive tools to evaluate the impact of xenobiotics on amphibians: the effects of anionic surfactant linear alkylbenzene sulfonate (LAS)

Abstract: Amphibian populations have been experiencing a drastic decline worldwide. Aquatic contaminants are among the main factors responsible for this decline, especially in the aquatic environment. The linear alkylbenzene sulfonate (LAS) is of particular concern, since it represents 84% of the anionic surfactants' trade. In Brazil, the maximal LAS concentration allowed in fresh waters is 0.5mgL, but its potential harmful effects in amphibians remain unknown. Therefore, this study aimed to analyze the effects of a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Linear Alkylbenzene Sulfonate, known as LAS (Figure 1), is one of the most widely used surfactants worldwide in the formulation of commercial detergents, the same in 2018 accounted for 84% of the anionic surfactant market [4,5], as it has an excellent acceptance in the market due to its high cleaning potential when compared to that of ordinary soap, the surfactant sodium lauryl ether sulfate (LESS) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Linear Alkylbenzene Sulfonate, known as LAS (Figure 1), is one of the most widely used surfactants worldwide in the formulation of commercial detergents, the same in 2018 accounted for 84% of the anionic surfactant market [4,5], as it has an excellent acceptance in the market due to its high cleaning potential when compared to that of ordinary soap, the surfactant sodium lauryl ether sulfate (LESS) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, increasing consumption of drinking water generates a large amount of wastewater with the development of the city and intensifies the pressure on the environment. Major pollutants of municipal wastewater come from human excrement, production activities, and waste from animals; and the main components are microorganisms, sugars, oils, proteins, urea, and fats, , of which 60% are organic matters (suspended matters accounting for more than 75%) . Once the pollutant content exceeds the carrying capacity of the water environment, serious environmental problems would arise and threaten human health, ecosystems, and the sustainable development of water resources. , Adsorption is an important method for pollutant control because of its simple operation and high efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported for humans chronically exposed to several agrochemicals (Sekhotha et al, 2016). Jones‐Costa et al (2018) demonstrated the relevance of employing morphological, physiological, and cellular features of the heart as biomarkers to evaluate the effects of xenobiotics in anuran tadpoles.…”
Section: Introductionmentioning
confidence: 99%